Heat Flow and Thermal Source of the Xi’an Depression, Weihe Basin, Central China - Xu, Wei; Tang, Xiaoyin; Cheng, Luyao; Dong, Ying; Zhang, Yuping; Ke, Tingting; Yu, Ruyang; Li, Yi (Frontiers in Earth Science, 2022)
The Xi’an Depression of the Weihe Basin, located in the transition zone where the North China, Qinling and Yangtze plates collide with each other, is an important area of geothermal energy utilization in China. Studies of heat flow and thermal sources are of great significance to the exploration and development of geothermal resources in this area. In this paper, 6 temperature logs boreholes, and 14 thermal conductivity samples have been used to study the geothermal gradient and terrestrial heat flow in the area. The results show that the geothermal gradients of Xi'an Depression range from 20.8 ℃/km to 49.1 ℃/km, with an average of 31.7±5.0 ℃/km. The calculated heat flow is 59.4–88.6 mW/m2, and the average value is 71.0±6.3 mW/m2, which indicates a high thermal background in the area. The high anomalous zones are near the Lintong-Chang'an Fault zone in the southeast, the Weihe Fault in the north, and the Fenghe Fault in the central Xi’an Depression. These deep and large faults not only control the formation of the Xi'an Depression but also provide an important channel for the circulation of groundwater and affect the characteristics of the shallow geothermal distribution. The temperature of the Moho in the Xi'an Depression ranges from 600 to 700°C, and the thermal lithosphere thickness is about 90-100 km. The characteristics of lithospheric thermal structure in Xi'an Depression indicate that the higher thermal background in the study area is related to lithospheric extension and thinning and asthenosphere thermal material upwelling.